「薄友誼」現象：數位原住民世代的網路社群交友觀及課程思維--以臺灣的大學生為例 "Thin Friendship": The Perspectives of the Generation of Digital Natives on Social Media Sites/ Online Dating Apps and Its Implications for Curriculum- Examples from College Students in Taiwan - 鄭英傑 Ying-Jie Jheng (Higher Education Foundation, 2021)
本研究旨在探討「數位原住民世代」對「網路社群交友」的了解、經驗與感 受。為達研究目的，本研究以臺灣的大學生（約出生於1999∼2003年）為研究對 象，透過訪談蒐集資料。根據研究發現，當前數位原住民世代對網路社群交友已司空見慣，不會特別給予「好」或「壞」的評價；再者，在這群年輕世代眼中，實體朋友與虛擬朋友的界線，已然模糊。植基於研究發現，本研究提出現今數位原住民世代已存在「薄友誼」現象，並衍生出四種相互滲透的友誼類型，除「現實朋友」與「現實陌生人」外，還出現「像陌生人的朋友（單向度朋友）」、「像朋友的陌生人（日拋型朋友）」的「薄友誼」；最後，則針對教育場域的課程實施，提供幾點思維。 The study was designed to reveal the understanding, experiences, and feelings of the generation of digital natives towards "social media sites / online dating apps." To this end, the study was targeted specifically at the current college students in Taiwan, approximately born in 1999 to 2003, and utilized interview technique to collect the empirical data. Based on the research findings, the current generation of digital natives, without being judgmental, has been familiar with making friends via social media sites /online dating apps. Consequently, the boundary between "face-to-face friends" and "internet friends," from the perspectives of the group, appears to be blurred. In light of the findings, the study further asserted that there has been a phenomenon of "thin friendship" emerging among the present generation of digital natives, and results in four "fluid" types of friends, including "face-to-face friends," "passing-by strangers," "stranger-like friends (one-dimension friends)," and "friend-like strangers (daily disposable friends)," and the later two are the so-called "thin friendship" in the study. Some educational implications for the curriculum were addressed in the end.